Activation of Silent Information Regulator 6 Signaling Attenuates Myocardial Fibrosis by Reducing TGFβ1-Smad2/3 Signaling in a Type 2 Diabetic Animal Model. Issue 1 (13th March 2022) - Yu, Liming; Wang, Jian; Dong, Xue; Hu, Yue; Luo, Linyu; Xue, Xiaodong; Wang, Yang
Abstract: Objective: Long-term diabetes can result in ventricular hypertrophic remodeling, tissue fibrosis, myocardial metabolic defection, and eventually, heart failure. Silent information regulator 6 (SIRT6) exerts beneficial effects against cardiovascular diseases. This study is aimed to investigate whether the direct regulation of myocardial SIRT6 signaling affects cardiac performance in the case of diabetes. Meanwhile, we sought to explore the underlying mechanisms. Methods: Sprague Dawley (SD) rats were used in this experiment. Briefly, type 2 diabetic animal model was generated by streptozotocin administration along with feeding a high-fat diet. The SD rats were randomly assigned to non-diabetic group, diabetic group, diabetic injected with empty adenoviral vectors group and diabetic injected with adenoviral vectors expressing SIRT6 group ( n = 10, respectively). The animals were kept for another 4 weeks before sacrifice. Cardiac performance was evaluated by echocardiography. Myocardial fibrosis was determined by Masson's trichrome staining. Myocardial SIRT6 signaling and fibrosis related molecules were measured by western blotting. Results: The diabetic myocardium exhibited markedly enhanced TGFβ1-Smad2/3-induced myocardial fibrosis and reduced SIRT6 and AMP-activated protein kinase (AMPK) signaling. After 4 weeks of SIRT6 adenoviral vector infection, myocardial tissues exhibited markedly enhanced SIRT6 and AMPK signaling. Additionally, myocardial fibrosis and TGFβ1-Smad2/3 signaling were both attenuated in the diabetic injected with adenoviral vectors expressing SIRT6 group. Conclusions: SIRT6-AMPK signaling suppressed the progression of tissue fibrosis in diabetes mellitus rats by inhibiting TGFβ1 and its downstream effector Smad2/3. SIRT6 might serve as an alternative therapeutic target for diabetes-related cardiovascular diseases.